An Analysis of plant awareness disparity within introductory Biology textbook images - Brownlee, Kristi; Parsley, Kathryn M.; Sabel, Jaime L. (Journal of Biological Education, 2021)
Plant awareness disparity (PAD, formerly plant blindness) is the tendency not to notice plants in one’s environment, which leads to the perspective that plants are unimportant. In this paper, we explore how plants and animals are represented in introductory biology textbooks to determine if these texts are contributing to PAD in undergraduate students. We ana lysed images from four texts that are commonly used as introductory biology textbooks for biology majors, and specifically focused on the introductory, genetics, and evolution chapters. We found that animals are chosen more often as examples of biological concepts in textbook images across all four textbooks, indicating that these texts are contribut ing to PAD. Textbook producers should focus on including a more equal number of plant and animal examples of biology concepts and processes, and instructors should bring in outside examples and images to supple ment those currently in texts that demonstrate a bias towards animals.